Pengembangan Sertifikasi Halal Pada IKM Makanan Dan Minuman Halal Melalui Forum IKM Ponorogo - Garnis Olivia Arcikasari; Ratna Yunita (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: Halal certification is very important for Muslims, especially in the food and beverage sector. in the Ponorogo area there are still IKM products that do not have halal certification. Therefore, it is necessary to develop so that these IKM products have halal certification. Research Methods: The research method used in this research is field research using a qualitative approach. Data and data sources taken in the form of primary and secondary data. Data collection techniques in this study used interviews and documentation. Results: The results of this study are that there are several developments carried out by the Ponorogo IKM Forum, including frequent involvement in various events, opening an UKM service corner, and Free Halal Certification (SEHATI), while the procedures for obtaining halal certification are for businesses that register must implement a Halal Assurance System (SJH), prepare file documents for business actors who want to extend or develop their business further, and for slaughterhouses must include the name of the slaughterer and include the method of slaughter either manually or mechanically. Conclusion: The Ponorogo IKM Forum has an important role in assisting business actors in developing IKM product in order to have halal certification for IKM products in Ponorogo.